DISTILLATION METHOD AND STRUCTURED PACKING - CHEN GUANG X; BILLINGHAM JOHN (2013)
A method of conducting a distillation process and a cross-corrugated structured packing for use in such a process in which ascending vapor phases and descending liquid phases are contacted in such packing. The cross-corrugated structured packing contains corrugated sheets fabricated of an open cell foam-like material. The liquid phase produces a liquid film descending along struts forming cells of the material and the vapor phase ascends within the cross-corrugated structured packing and enters the cells and contacts the liquid film. The cross-corrugated structured packing is configured such that a superficial velocity at which ambient air would flow through the cross-corrugated structured packing at a pressure drop of 0.3'' wc/ft is no greater than 20 times a reference superficial velocity at which the ambient air would flow through the foam-like material making up the corrugated sheets at the same pressure drop to ensure that vapor enters the cells of the foam-like material.